An Examination of the Relationship between Team Cohesion and Individual Anxiety among Recreational Soccer Players - Oh, Eungwang; Gill, Diane (Journal of Amateur Sport, 2017)
The purpose of this research was to examine the relationship between cohesiveness and competitive state anxiety and the contribution of cohesion to the prediction of competitive state anxiety among recreational soccer players. The research, which was conducted over two studies with recreational soccer players (n=47 in Study 1; n=88 in Study 2), revealed negative relationships between sub-dimensions of cohesion and cognitive and somatic state anxiety. Further, individual attraction to the group-task (ATG-T) contributed significantly to the prediction of state anxiety beyond the contribution of competitive trait anxiety. The findings suggest that recreational soccer participants with high ATG-T are likely to have low competitive state anxiety.